Evaluation of Proton Therapy Accuracy Using a PMMA Phantom and PET Prediction Module - Zhang, Junyu; Lu, Yan; Hsi, Wenchien; Zhang, Jiangang; Sheng, Yinxiangzi; Shi, Leijun; Wang, Weiwei; Lu, Jiade; Zhou, Rong; Cheng, Jingyi (Frontiers in Oncology, 2018)
Purpose: Positron emission tomography (PET) scanning is a widely used method of proton therapy verification. In this study, a proton radiotherapy accuracy verification process was developed by comparing predicted and measured PET data to verify the correctness of PET prediction and was tested at the Shanghai Proton and Heavy Ion Center. Method: Irradiation was performed on a polymethyl methacrylate (PMMA) phantom. There were two dose groups, to which 2 Gy and 4 Gy doses were delivered, and each dose group had different designed dose depths ranging from 5 cm to 20 cm. The predicted PET results were obtained using a PET prediction calculation module. The measured data were collected with a PET/computed tomography device. The predicted and measured PET data were normalized to similar PET amplitude values before comparison and were compared using depth and lateral profiles for the position error. The error was evaluated at the position corresponding to 50% of the maximum on the PET curves. The mean and standard deviation were calculated based on the data sampled in the scoring area. Results: In the depth comparison, the 2 Gy and 4 Gy dose cases yielded similar mean depth errors between 1 mm and -1 mm, and the deviation was less than 2 mm. In the lateral comparison, the 2 Gy cases had a mean lateral error around 1 mm, and the 4 Gy cases had a mean lateral error less than 1 mm, with a standard deviation less than 1 mm for both the 2 Gy and 4 Gy cases. Conclusion: The comparison of these PMMA phantom cases revealed good agreement between the predicted and measured PET data, with depth and lateral position errors less than 2 mm in total, considering the uncertainty. The comparison results demonstrate that the PET predictions obtained in PMMA phantom tests for single proton beam therapy verification are reliable and that the research can be extended to verification in human body treatment with further investigation.